2020
DOI: 10.3390/rs12030342
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Model Grid Size on the Estimation of Surface Fluxes Using the Two Source Energy Balance Model and sUAS Imagery in Vineyards

Abstract: Evapotranspiration (ET) is a key variable for hydrology and irrigation water management, with significant importance in drought-stricken regions of the western US. This is particularly true for California, which grows much of the high-value perennial crops in the US. The advent of small Unmanned Aerial System (sUAS) with sensor technology similar to satellite platforms allows for the estimation of high-resolution ET at plant spacing scale for individual fields. However, while multiple efforts have been made to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 66 publications
0
16
0
1
Order By: Relevance
“…It is also common to use thermal sensors since water stress causes stomatal closure that reduces transpiration and evaporative cooling and increases temperature [23]. In this way, data from thermal sensors were combined with RGB [21] or multispectral sensors [24,25] to take advantage of the information provided in different areas of the spectrum and the higher spatial resolution of such sensors.…”
Section: Sensors and Vegetation Indices Usedmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also common to use thermal sensors since water stress causes stomatal closure that reduces transpiration and evaporative cooling and increases temperature [23]. In this way, data from thermal sensors were combined with RGB [21] or multispectral sensors [24,25] to take advantage of the information provided in different areas of the spectrum and the higher spatial resolution of such sensors.…”
Section: Sensors and Vegetation Indices Usedmentioning
confidence: 99%
“…Lower altitudes result in images with finer spatial resolution, but require longer flights and demand higher computational times for image processing [35]. Therefore, evaluation of flight altitude and spatial resolution was a central point in some investigations of this SI [16,24,27,29,36], being a usual objective to resample UAV images to spatial resolutions similar to those of common satellites, e.g., 5 m of Rapideye, 10 m of Sentinel-2, and 30 m of LANDSAT, in order to study the potential of using such satellite platforms instead of UAV for specific agro-forestry goals. Thus, Iizuka et al (2019) [16] discovered that CC estimation was affected by spatial resolution and coarser resolutions showed stronger correlation with manually delineated data in an RGB orthomosaic, concluding that the satellite images could be feasible for this purpose.…”
Section: Spatial Resolution Requerimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A selected list of efforts are mentioned here: a) Landsat-UAV data harmonization (Aboutalebi et al, 2018b) to evaluate potential biases on UAV information and direct comparison to Landsat satellite products; b) Atmospheric impact on UAS thermal information (Torres-Rua, 2017), to address atmospheric conditions with the advent of stronger UAVs (e.g. BVLOS); c) UAV optical and thermal spectral and spatial uncertainty impact (McKee et al, 2018) to evaluate potential issues caused by spectral and location biases towards estimation of evapotranspiration; d) Shadow impact on UAS optical and thermal products (Aboutalebi et al, 2019a), to evaluate shadow effect in orchards and vineyards on vegetation indices, to biomass and surface energy balance; e) Estimation of energy balance fluxes for vineyards crops using UAS (Nieto et al, 2015;Nieto et al, 2019), an adaptation of the TSEB approach to the uniqueness of vine orchards; f) Soil water estimation using UAS (Hassan-Esfahani et al, 2015), application of machine learning approaches for soil water content; g)Yield and biomass estimation using UAS (Aboutalebi et al, 2018a); h) use of point cloud in estimation of evapotranspiration (Aboutalebi et al, 2020); and i) Pixel size impact on the estimation of ET using UAV (Nassar et al, 2020), to assess the changes in ET estimation accuracy for energy balance and ET with fine and coarser pixels. These studies, along with other researchers (Kustas et al, 2018), provide the necessary support for additional UAV development such as use of beyond line of sight UAVs and drone swarm, real-time agricultural applications, and integration of UAV and satellite information for agriculture.…”
Section: Utah Utah State University ─ Aggieair Uav Research Programmentioning
confidence: 99%
“…Small Unmanned Aerial Systems (sUAS) operated under the Federal Aviation Administration (FAA) Part 107 licensing outfitted with optical sensors are increasingly used in vegetation remote sensing [6] and precision agriculture applications [7]. More recently, however, comparative studies of EOS and sUAS observations of crop water stress have shown significant spatiotemporal uncertainty in coarser EOS data [8,9].…”
Section: Introductionmentioning
confidence: 99%